Assessment of Post-Operative Complications after Radial Recurrent Artery Flap for Management of Wound Coverage in and Around the Elbow Region (Bangladesh Medical Journal, 2024)
Complex elbow wound management is a common issue of reconstructive surgery which deals with burns (electric and flame burn), road traffic accidents (RTA), machineries and industrial accidents, tumor excision, the release of post-burn scar contracture, complications related to orthopedic reconstruction etc. A stable soft tissue cover is required for reconstructive purposes for such wounds management and for that reason surgeons apply suitable procedure and consider wound aetiologies to meet better outcome. Surgeons also permit the early elbow mobilization to preserve a range of motion after complex elbow wound management. Radial recurrent artery flap, in particular, provides durable coverage for medium-sized elbow defects as well as an early range of motion of the elbow joint. Some complications like marginal and partial flap necrosis are observed in some of the cases. The aim of the study was to assess the clinical outcome and complications after radial recurrent artery flap for the management of wound coverage in and around the elbow region. This is a prospective type of observational study conducted in the Department of Plastic Surgery, Dhaka Medical College and Hospital (DMCH), Dhaka. Twenty patients were selected according to inclusion and exclusion criteria over 17 months from October 2016 to February 2018. The patients were kept under follow-up of at least 2 months postoperatively. Findings of observation were recorded in a preformed data collection sheet and all data were compiled in a master table first. Statistical analysis of the results was obtained by using statistical package for social science (SPSS), version- 17. In this study, the mean age of the patients was 25.4 years. The age range was 05 years to 50 years. Maximum patients (40%) were in age group 16 to 25 years. Of the injured patients, male – female ratio was 4:1. More than half of the injuries (55%) were caused by electric burn; other injuries were trauma (15%), flame burn (10%), contact burn (05%), and 15% by different causes. Radial recurrent artery flap was used to cover the cubital fossa in 13 patients (65%), the posterior aspect of the elbow in 5 patients (25%), and amputation stump in 02 patients (10%). The cubital fossa was the most used site in 13 patients. Here, the mean dimension of the wound was 80.28 cm2 and the mean dimension of the flap was 70.43cm2. Among 20 patients, 16 patients showed no complication, marginal flap loss in one patient, partial flap necrosis in two patients, and total flap loss in one patient was observed. No history of graft loss and the donor site of the skin graft healed well. One case showed marginal flap loss, which is managed conservatively and healed by secondary intention. Two cases showed partial flap loss and another case showed total flap loss which is managed by excision of non-viable part followed by STSG. In 17 (85%) cases donor sites of flaps are closed primarily. One patient (05%) needed primary closure and STSG. Two patients (10%) needed STSG to cover the donor site. In most of the cases, about 80% showed excellent outcomes. Good outcomes in three cases (distal marginal and partial flap loss) and poor outcomes in one case (total flap loss) were observed. This study showed that Radial Recurrent Artery Flap is a good option for coverage of soft tissue defects in and around the elbow joint. It is a single-stage procedure allowing early mobilization and thereby preventing stiffness of the elbow joint. It also showed the rise of some complications that might be uncomfortable for patients.Bangladesh Med J. 2023 Sept; 52(3): 41-46